A Critique on the Practice of Filial Piety in Confucian Culture - Kim, Donghyun (Archīum Ateneo, 2024)
The concept of filial piety has initially served as a social ethic in order to sustain the hierarchical family relationships in Confucian culture. Filial piety has also been implemented as an ideological weapon in an attempt to inculcate broader political virtue into the minds of people in Confucian culture. In essence, the everyday practice of filial piety denotes a mode of concrete ethical life, which fundamentally binds participants’ way of thinking to a particular tradition. However, such binding is not the result of a discursive procedure that provides a rational grounding to social and political authority. Given the difficulties with accepting the taken-for- granted ethical value in a particular culture—namely, that the practice of filial piety is an implicit rejection of the reciprocal and free relationship between parents and their children—the critical examination of ethical life through the application of moral standards (the universal principle) should be reconsidered. Thus, the structure of social hierarchy is a common phenomenon in Confucian culture that has had a profound influence on people’s perceptions. The practical purpose of critique depends on human emancipation, which suggests possibilities for social change in terms of how human beings live a free life in society. To this end, this paper critically analyzes the efficacy of filial piety in Confucian culture by observing Habermas’s theories of communicative action and discourse ethics. Ultimately, this paper argues that the tenet of filial piety in Confucian culture, in general, and the practice of South Korean Confucian culture, in particular, amounts to a rejection of the “iron cage” of the taken-for-granted tradition by virtue of the normative grounding of justification.